Methods of teaching the subject "Cohesive parts" in primary school lessons - Mamatova Dilafroz Zafarovna (Indonesian Journal of Public Policy Review, 2022)
The article discusses the topic of cohesive parts given in primary school textbooks. Analyzes the methods of teaching cohesive parts, the methods used.